Standardizing OER Electrocatalyst Benchmarking in Aqueous Electrolytes: Comprehensive Guidelines for Accelerated Stress Tests and Backing Electrodes - Zlatar, Matej; Escalera-López, Daniel; Rodríguez, Miquel Gamón; Hrbek, Tomáš; Götz, Carina; Mary Joy, Rani; Savan, Alan; Tran, Hoang Phi; Nong, Hong Nhan; Pobedinskas, Paulius; Briega-Martos, Valentín; Hutzler, Andreas; et al. (ACS Catalysis, 2023)
The scarcity of iridium, needed to catalyze the sluggish oxygen evolution reaction (OER), hinders large-scale hydrogen production with proton exchange membrane water electrolyzers (PEMWEs). Crucial steps require reducing its loading while improving its overall activity and stability. Despite knowledge transfer challenges, cost and time constraints still favor aqueous model systems (AMSs) over real devices for the OER electrocatalyst testing. During AMS testing, benchmarking strategies such as accelerated stress tests (ASTs) aim at improving catalyst lifetime estimation compared to constant current loads. This study systematically evaluates a commercial Ir catalyst by modifying both AST parameters and the employed backing electrodes to examine their impact on activity-stability relationships. A comprehensive set of spectroscopy and microscopy techniques, including in situ inductively coupled plasma mass spectrometry, is employed to monitor Ir and backing electrode modifications. Our findings demonstrate that the choice of both lower potential limit (LPL) in ASTs and backing electrode significantly influences the estimation of Ir-based electrocatalysts’ activity and stability. Unique degradation mechanisms, such as passivation, redeposition on active sites, and contribution to the OER, were observed for different backing electrodes at varying LPLs. These results emphasize the importance of optimizing parameters and electrode selection in ASTs to accurately assess the electrocatalyst performance. Furthermore, they establish the foundation for developing relevant standardized test protocols, enabling the cost-effective development of high-performance catalysts for PEMWE applications.
CRIS-Team Scopus Importer:2023-12-08
Keywords: accelerated stress test; boron-doped diamond; dissolution; glassy carbon; gold; iridium; oxygen evolution reaction